Managing Dissent - Timothy Zick (Washington University Law Review, 2018)
In his insightful new book, Managed Speech: The Roberts Court’s First Amendment (2017), Professor Greg Magarian criticizes the Roberts Court for adopting a “managed speech” approach in its First Amendment cases. According to Professor Magarian, that approach gives too much power to private and governmental actors to manage public discourse, constrain dissident speakers, and instill social and political stability. This Article argues that at least insofar as it relates to many forms of public dissent, the managed speech approach is both deeply rooted in First Amendment jurisprudence and culturally prevalent. Historically, First Amendment jurisprudence has expressed support for narrowly managed public dissent. Expressive activities that pose no threat of actual disruption, and that do not risk undermining social and political stability, have been granted a preferred position. Managed speech attitudes and principles are part of our contemporary culture and politics. Public and private actors manage dissent from statehouses, to college campuses, to National Football League stadiums. Legislatures and executive officials have sought to curb public protests, universities have acted to limit campus dissent, and the NFL has faced pressure to dismiss players who refuse to stand at attention during the playing of the national anthem. In these contexts, officials and private institutions have sought to curb, tame, and marginalize public dissent. Efforts to manage dissent cut sharply against the alternative “dynamic diversity” model that Professor Magarian advocates in his book. Achieving that ideal will take more than a few Supreme Court decisions. It will require changing political and cultural attitudes concerning the meaning and value of public dissent.
Keywords: Managed Speech; Roberts Court; First amendment; Greg Magarian; Public dissent